(3GdGMJHGc aj Cf Gdfhe dG jVGO efWb hdG EOQGcs - (3fhQ GdOjf EHQGgje Hf MSf GdcQOi GdchQGfis; (3eMeO Hf GdMSf GdCUagGfj GdTQhGfj , edG ejQRG,J (B1099 (3g` s
(3ChdgG (B:s
(3GeG HYO abO PcQJe ai GdcJGH GdSDGd GdePchQ SGHbkG s
(3BNQgG (B:s
(3hGdeSCdI bGHdI ddHSW hdcf GdhbJ cKjQ GdGTJZGd hajeG PcQ caGjI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B90 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B194s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs